De laatmiddeleeuwse crisis van de overheidsfinanciën en de financiële revolutie in Holland - Zuijderduijn, Jaco (BMGN - Low Countries Historical Review, 2010)
The Late Medieval Crisis of Government Finance and the Financial Revolution in HollandHistorians of the Dutch Revolt have suggested that the success of the rebellious provinces can be explained by sixteenth-century financial innovations that improved the creditworthiness of the States of Holland. This article claims that this development was triggered by a severe crisis of public finance in these States at the end of the fifteenth century. An analysis of the ensuing reorganization shows that some of these innovations were first introduced as a means of crisis management. This article uncovers some of the elements that allowed the States to create provincial debt on a more structural basis after 1515, during Holland’s ‘financial revolution’.